2023
DOI: 10.1007/s11033-023-08390-9
|View full text |Cite
|
Sign up to set email alerts
|

Overloaded axial stress activates the Wnt/β-Catenin pathway in nucleus pulposus cells of adult degenerative scoliosis combined with intervertebral disc degeneration

Abstract: Background Intervertebral disc degeneration (IVDD) is the initiating factor of adult degenerative scoliosis (ADS), and ADS further accelerates IVDD, creating a vicious cycle. Nevertheless, the role of the Wnt/β-Catenin pathway in ADS combined with IVDD (ADS-IVDD) remains a mystery. Accordingly, this study was proposed to investigate the effect of axial stress on the Wnt/β-Catenin pathway in nucleus pulposus cells (NPCs) isolated from DS-IVDD patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…With the progression of IDD, β-catenin positive cells also increase (Iwata et al 2015 ). Cai Z et al (Cai et al 2023 ) revealed that the activation of Wnt//β-catenin signaling pathway inhibits the NPCs proliferation and promote their apoptosis, thereby accelerating the progress of IDD. Shi Z et al (Shi et al 2022 ) found that high hydrostatic pressure promoted apoptosis and inhibited the viability of human NPCs by activating Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the progression of IDD, β-catenin positive cells also increase (Iwata et al 2015 ). Cai Z et al (Cai et al 2023 ) revealed that the activation of Wnt//β-catenin signaling pathway inhibits the NPCs proliferation and promote their apoptosis, thereby accelerating the progress of IDD. Shi Z et al (Shi et al 2022 ) found that high hydrostatic pressure promoted apoptosis and inhibited the viability of human NPCs by activating Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Kondo N et al (Kondo et al 2011 ) found that Wnt/β-catenin plays a key role in IVD development through Wnt/β-catenin reporter (TOPGAL) mice. Cai Z et al (Cai et al 2023 ) found that the activation of Wnt/β-catenin signaling pathway decreases the viability of NPCs and increases their apoptosis rate. Interestingly, S100A6 expression was synergistic with β-catenin in eutopic endometrial stromal cells (Liu et al 2015 ; Zhang et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%